The Hippo-YAP/β-catenin signaling axis coordinates odontogenic differentiation in dental pulp stem cells: Implications for dentin-pulp regeneration. - Chang Chen; Qiqi Yun; Juanli Ran; Ziyao Zhou; Pengxiang Zhang; Rong Li (PLoS ONE, 2025)
Objective This study investigated the interplay between Hippo-YAP and β-catenin signaling in regulating odontogenic differentiation of human dental pulp stem cells (DPSCs) and explored its potential implications for dentin-pulp regeneration. Methods Using lentivirus-mediated YAP overexpression/silencing, β-catenin siRNA knockdown, and pharmacological Wnt inhibition (via WIF-1), we assessed DPSC proliferation, migration, mineralization, and molecular markers (via qRT-PCR, immunofluorescence). In vivo validation employed subcutaneous transplantation of DPSC-seeded scaffolds in immunocompromised mice. Results YAP activation enhanced DPSC proliferation (1.44-fold), migration (1.39-fold), invasion (1.54-fold), and differentiation, as evidenced by elevated ALP activity (1.46-fold) and mineralization (1.36-fold). We observed transcriptional upregulation of odontogenic markers (RUNX2, DSPP, DMP1, OCN, ALP) and Wnt pathway components (β-catenin, Cyclin D1, c-Myc). Immunofluorescence revealed coordinated YAP and β-catenin expression patterns during differentiation. β-catenin silencing or Wnt inhibition abolished YAP-mediated functional enhancements and simultaneously suppressed YAP expression, partially confirming bidirectional regulation. In vivo, YAP-overexpressing DPSCs exhibited 1.27- to 1.62-fold induction of dentin-specific markers and β-catenin, whereas YAP silencing impaired these markers expression. Conclusions Our findings demonstrate that coordinated YAP and β-catenin signaling drives DPSC odontogenesis, with potential implications for dentin regeneration. Although reciprocal regulation is evident, direct molecular interactions require further validation.